Speak with Confidence: A Journey to Effective Communication - Purwanti Taman (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Rooted in the growing urgency to align vocational education with real-world demands, this study investigates a targeted communication training program aimed at enhancing public speaking confidence among Indonesian vocational high school students. Many students face persistent struggles in formal speaking situations. not due to lack of knowledge, but because of low self-perceived communication competence and anxiety. To address this, the communication training program was conducted as a community service initiative by Universitas Pamulang at SMKS Kusuma Bangsa. Employing a qualitative-descriptive method informed by Creswell (2014) framework, the program integrated experiential learning strategies such as mock interviews, motivational media, and communicative games. Observational data, self-reflections, and teacher evaluations revealed marked improvements in students’ articulation, composure and use of formal language. The program not only reduced speaking anxiety but also cultivated social and emotional readiness for professional communication. These findings highlight the value of immersive, learner-centered communication training in preparing vocational students for the linguistic and interpersonal demands of the modern workplace.